Post-Event Analysis of The Influence of President Donald Trump's Tweet Sentiment on the Abnormal Returns, Trading Volume Activity, and Volatility of S&P 500 Companies - Ar Rasyid, Muhammad Angga Farizki (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the impact of tweet sentiment—both positive and negative—and its effect on the day the tweet is posted (event day) and the following day (post-event day) on abnormal return, trading volume activity, and volatility of companies listed on the Standard & Poor’s 500 stock exchange that were directly mentioned in President Donald Trump’s tweets between 2016 and 2019. Using panel data consisting of 326 time series observations and 29 company units, the results indicate a significant positive influence of sentiment on volatility, where positive sentiment tends to reduce market uncertainty. Additionally, there is a delayed effect of time on abnormal return, suggesting that the market responds slowly to information received. These findings support the semi-strong form of the Efficient Market Hypothesis, which posits that investors are capable of processing public information selectively but not operate full alignment when making decisions in the stock market.